# Evaluating the following integral: $\int \frac{x^2}{\sqrt{x^2 - 1}} \text{ d}x$

For this indefinite integral, I decided to use the substitution $x = \cosh u$ and I've ended up with a $| \sinh u |$ term in the denominator which I'm unsure about dealing with: $$\int \dfrac{x^2}{\sqrt{x^2 - 1}} \text{ d}x \ \overset{x = \cosh u}= \int \dfrac{\cosh^2 u \cdot \sinh u}{\left| \sinh u \right|} \text{ d}u$$ How would I deal with the denominator?

• Just simplify $\sinh u$. Anyway, title and question is different. – Tunk-Fey May 30 '14 at 11:05
• How would I do that? I'm trying to find the indefinite integral and I know that $$\left| \sinh u \right| = \begin{cases} +\sinh u, & u \geq 0 \\ -\sinh u, & u < 0 \end{cases}$$ (Thanks for pointing that out!) – Khallil May 30 '14 at 11:06
• Just take the principal root. – Tunk-Fey May 30 '14 at 11:08
• If I take the principle root, won't I be ignoring the region $u < 0$, meaning the integral won't be indefinite? – Khallil May 30 '14 at 11:10
• When dealing with indefinite integrals, don't sweat it. Assume it's $\sinh u$ and go on. – Mark Fantini May 30 '14 at 11:11

On your method, you can use the sign function $\mathrm{sgn}$ which can be used as $$|\sinh (u)| = \mathrm{sgn} (\sinh u) \sinh u$$ Your integral becomes $$\int \cosh^2u \, \mathrm{sgn}(\sinh (u)) du = \int \frac 1 2 ( 1+ \cosh (2u)) \mathrm{sgn}(\sinh u) du$$ this equals $$\frac 1 2u \, \mathrm{sgn}(\sinh u)+ \frac 1 4 \sinh (2u) \mathrm{sgn}(\sinh u)$$ Upon simplification, using inverse hyperbolic substitution back to $x$ substitution, you get $$\frac 1 2 \log |x + \sqrt{x^2 - 1}| + \frac 1 2 x\sqrt{1-x^2}$$ also the relation $\mathrm{sgn}(\sinh u) \sinh u = \sqrt{1 - x^2}$ and $\mathrm{sgn}(\sinh u) u = |u|$ (note that I am only taking positive values multiplied with $\mathrm{sgn}$) and $|x + \sqrt{x^2 - 1}|\ge 1$ for $x\ge -1$

• This is just the kind of thing that I've been looking for. From your working, I'm guessing the $\text{sgn}$ function can be taken out as a constant? Also, is this true? $$\dfrac{1}{\text{sgn}(\sinh u)} = \text{sgn}(\sinh u)$$ – Khallil May 30 '14 at 11:48
• @Shisui yes!! you can conclude that from here. I found this function easy to integrate this type of integral. – Santosh Linkha May 30 '14 at 11:50
• How would you calculate the definite integral between $0$ and $2\pi$ of that integral with the signum function? – Khallil May 30 '14 at 12:10
• There is simply no reason to not assume that $\sinh u\geq 0$. Basically, just insist that $u\geq 0$. Keeping track of the sign is way more painful. – Thomas Andrews May 30 '14 at 12:11

Alternatively, we can solve it by just doing a trick:

$$\dfrac{x^2}{\sqrt{x^2 - 1}} = \dfrac{x^2 - 1 + 1}{\sqrt{x^2 - 1}} = \sqrt{x^2 - 1} + \dfrac{1}{\sqrt{x^2 - 1}}.$$

Then let $x = \sec\theta$.

$\dfrac t{|t|}=\pm1$, depending on whether t is positive or negative. Now, $\displaystyle\int a\cdot f(u)~du=a\cdot\int f(u)~du$.

In this case, $a=\pm1$. As far as the actual integration is concerned, use $\cosh^2x=\dfrac{1+\cosh2x}2$

I found another excellent answer from @MartinSleziak :3

Let us denote your function by $f(x)$. Suppose that we are able to solve the problem for $[1,\infty)$, i.e. that we can find the primitive function $F$ such that $F'(x)=f(x)$ for each $x\in[1,\infty)$.

Now we can notice that $f(x)=f(-x)$.

So if we take $G(x)=-F(-x)$ for $x\le-1$,, then $G'(x)=F'(-x)=f(-x)=f(x)$.

So from the primitive function on $[1,\infty)$ you can get primitive function on $(-\infty,-1]$ simply by using the fact that you want the primitive function to be odd. (The original function was even.)

Of course, then you can add constants, so you can get $G(x)+C_1$ and $F(x)+C_2$.

But if you insist that you want to try to do this by substitution, you could use $x=-\cosh u$.

Clearly, $-\cosh u$ attains exactly the values in the interval $(-\infty,1]$.

First assume that $x=\tan u$, after replacing this value, $dx=du/(\cos u)^2$ in terms of $u$ variable, the integral will be $$I=\int\cos u (\sin u)^2 du.$$

Then replace $sin u= v$, you gotta find that $\cos u du=dv$. With v variable, we will have $I=\int v^2 dv$ and the result (answer) in terms of $v$ variable is $\tfrac{v^3}3+c$ going back to $u$ variable, we have this solution $\tfrac{\sin^3 u}3+c$ and by replacing $u$ by its value $\arctan x$, the result is: $$\boxed{\displaystyle\dfrac13 \sin ^3(\arctan x)+c}$$

• Please use proper syntax. Here is a MathJax Tutorial to help you. – user88595 May 30 '14 at 12:49